Application of soy protein coatings and their effect on the quality and shelf-life stability of beef patties. Issue 11 (7th February 2015) - Guerrero, Pedro; O'Sullivan, Maurice G.; Kerry, Joe P.; de la Caba, Koro
<x xml:space="preserve">Abstract</x> There was no significant change in lipid oxidation up to day 10 of storage for soy-protein-coated samples.